The Interaction of Variables Affecting Definitional Skills: Extending Previous Research on Word Definitions - Zoe Gavriilidou; Angelos Markos; Chryssa Dourou (Journal of Language and Education, 2022)
Background and Purpose. Given that definitional skills are closely related to literacy and reading comprehension, the purpose of this study was to extend the existing literature in definitional skills by empirically investigating the effect of new parameters that may affect word definitions and definitional types of content and form, such as grammatical categories, word structure, and semantic characteristics.